Pengaruh Karakteristik Individu dan Kompensasi terhadap Turnover Intention - Ratih Prameswari Wulan Asih (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This study aims to determine the Individual Characteristics and Compensation for Turnover Intention at the Perisai Husada Main Clinic. This research is categorized as descriptive and verification research as a quantitative approach with an instrument in the form of a questionnaire. The sampling technique in this study used saturated samples because all 55 employees of the Perisai Husada Main Clinic were made into the population. Data collection using questionnaires and interviews. Test the validity of the instrument using Pearson's product moment while the reliability test with the Alpha cronbanch with the help of SPSS 25. 0 Measuring instruments prove to be valid and reliable for research instruments. Hypothesis testing of this study uses multiple linear regression analysis. The results of the study prove that: (1) Individual characteristics significantly positive effect on Turnover Intention with a value of β = 0.394 and sig = 0,000, the contribution of individual characteristics to Turnover Intention 0.434 = 43.4%; (2) Compensation has a positive effect on Turnover Intention with a value of β = 0.530 and sig 0,000, contribution of Compensation to Turnover Intention 0.569 = 56.9%; (3) Individual Characteristics and Compensation have a significant positive effect on Turnover Intention with a result of R² = 0.622. This means that Individual Characteristics and Compensation is 62.2% while the remaining 27.8% is influenced by other variables outside the variables studied. Abstrak. Penelitian ini bertujuan untuk mengetahui Karakteristik Individu dan Kompensasi terhadap Turnover Intention pada Klinik Utama Perisai Husada. Penelitian ini di kategorikan sebagai penelitian deskriptif dan verikatif sebagai pendekatan kuantitatif dengan instrument berupa kuesioner. Teknik pengambilan sampel dalam penelitian ini menggunakan sampel jenuh karena seluruh karyawan Klinik Utama Perisai Husada sebanyak 55 orang dijadikan populasi. Pengumpulan data menggunakan kuesioner dan wawancara. Uji validitas instrumen dengan menggunakan product moment pearson sedangkan uji reliabilitas dengan cronbanch Alpha dengan bantuan SPSS 25. 0 Alat ukur terbukti valid dan reliabel untuk instrument penelitian. Uji hipotesis penelitian ini menggunakan analisis regresi linear berganda. Hasil penelitian membuktikan bahwa: (1) Karakteristik Individu berpengaruh positif signifikan terhadap Turnover Intention dengan nilai β= 0,394 dan sig = 0,000, kontribusi karakteristik individu terhadap Turnover Intention 0,434 = 43,4%; (2) Kompensasi berpengaruh positif terhadap Turnover Intention dengan nilai β=0,530 dan sig 0,000, kontribusi Kompensasi terhadap Turnover Intention 0,569 = 56,9%; (3) Karakteristik Individu dan Kompensasi berpengaruh positif signifikan terhadap Turnover Intention dengan hasil R² = 0,622. Hal ini berarti Karakteristik Individu dan Kompensasi 62,2% sedangkan sisanya 27,8% dipengaruhi oleh variabel lain di luar variabel yang diteliti.